2014
DOI: 10.1093/treephys/tpt118
|View full text |Cite
|
Sign up to set email alerts
|

Axial vessel widening in arborescent monocots

Abstract: Dicotyledons have evolved a strategy to compensate for the increase in hydraulic resistance to water transport with height growth by widening xylem conduits downwards. In monocots, the accumulation of hydraulic resistance with height should be similar, but the absence of secondary growth represents a strong limitation for the maintenance of xylem hydraulic efficiency during ontogeny. The hydraulic architecture of monocots has been studied but it is unclear how monocots arrange their axial vascular structure du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 28 publications
2
18
0
Order By: Relevance
“…Empirical data coincide strikingly with this prediction, with within‐individual widening in the shoot‐root system in all cases so far being close to 0.2 (0.1–0.3) (Anfodillo et al ., 2006, 2012; Coomes et al ., 2007; Petit et al ., 2008, 2009, 2011, 2014; Bettiati et al ., 2012; Petit & Crivellaro, 2014; Echeverría et al ., 2019; Fajardo et al ., 2019; Williams et al ., 2019). This result strongly suggests that natural selection has placed a premium on vascular designs with conduits that widen from tip to base in a way that minimizes the increase in hydraulic resistance that would otherwise arise as plants grow taller.…”
Section: Evidence For Adaptation: Hydraulic Optimality Modelsmentioning
confidence: 99%
“…Empirical data coincide strikingly with this prediction, with within‐individual widening in the shoot‐root system in all cases so far being close to 0.2 (0.1–0.3) (Anfodillo et al ., 2006, 2012; Coomes et al ., 2007; Petit et al ., 2008, 2009, 2011, 2014; Bettiati et al ., 2012; Petit & Crivellaro, 2014; Echeverría et al ., 2019; Fajardo et al ., 2019; Williams et al ., 2019). This result strongly suggests that natural selection has placed a premium on vascular designs with conduits that widen from tip to base in a way that minimizes the increase in hydraulic resistance that would otherwise arise as plants grow taller.…”
Section: Evidence For Adaptation: Hydraulic Optimality Modelsmentioning
confidence: 99%
“…A study on leaves of ash species by Petit and Anfodillo (2013) showed variation in conduit diameter along the leaf rachis, with vessel diameter widening from the apical leaflet base to the petiole, suggesting that vessel diameter scales with leaf length. Variation of conduit diameter with path length is theoretically predicted by the West, Brown, and Enquist (WBE) model for tree stems (West et al , 1999) and this has been supported by several studies conducted on different species (Anfodillo et al , 2006; Olson et al ., 2014, 2018; Petit et al , 2014). The WBE model predicts that conduit widening from the top of the tree to its base is involved in compensating for the potential increase of hydraulic resistance imposed by increasing height (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, vascular conduits of bamboo xylem have to remain functional throughout the ontogeny of a bamboo culm. Bamboos consequently have great ability to avoid cavitation ( Cochard et al, 1994 ; Cao et al, 2012 ; Petit et al, 2014 ); root pressure mechanisms may contribute to repairing embolized conduits at night ( Cao et al, 2012 ). Such features and structural traits of bamboos may also lead to particular water use patterns.…”
Section: Introductionmentioning
confidence: 99%